Screening method of vein quartz type high-purity quartz for photovoltaic crucible and application of screening method
Through the multi-dimensional comprehensive evaluation of high-purity quartz for photovoltaic crucibles, the problems of different evaluation and screening standards and relying on traditional testing in the existing technology are solved, and efficient resource utilization and cost control are achieved.
Patent Information
- Application Number
- CN202510105791.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art lacks unified standards in the evaluation and screening of high-purity quartz sand for photovoltaic crucibles, and over-reliance on traditional crucible testing is difficult to meet the demands of single crystal silicon manufacturing for product quality and cost control.
A comprehensive evaluation system is used to screen vein quartz-type high-purity quartz for photovoltaic crucibles, including analyzing mineral composition, mineral inlays, micromorphology, chemical composition and lattice impurities, and its applicability is determined through multi-dimensional ratings.
It effectively solves the problems of different evaluation and screening standards for high-purity quartz sand and over-reliance on traditional crucible testing, significantly reduces unnecessary waste of manpower, material resources and financial resources, and realizes efficient utilization of resources.
Smart Images

Figure CN119534809A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-purity quartz, and in particular to a screening method for vein quartz type high-purity quartz for photovoltaic crucibles and application thereof. Background Art
[0002] High-purity quartz is a key basic material for strategic emerging industries such as new generation information technology, new energy and high-end equipment, and is widely used in photovoltaics, semiconductors, electric light sources and optical fiber communications. With the rapid development of the photovoltaic industry, the demand for high-purity quartz sand for photovoltaic crucibles is also growing.
[0003] High-purity quartz sand for photovoltaic crucibles has strict requirements on purity, impurity elements, inclusions, particle size and other indicators. However, there is currently no unified standard in China. Impurity elements are only regulated in T / CEMIA 005-2018 "Production Specifications for Quartz Crucibles for Photovoltaic Monocrystalline Silicon Growth". In addition, in order to verify whether the quartz sand is suitable for the production of photovoltaic crucibles, a crucible test is required, which is difficult to meet the needs of the monocrystalline silicon manufacturing industry for product quality and cost control.
[0004] Therefore, establishing an evaluation system for high-purity quartz for photovoltaic crucibles is of great practical significance for optimizing the development and utilization of high-purity quartz resources and helping companies reduce costs and improve product quality.
[0005] The Chinese invention patent application with publication number CN116159665A discloses a method for screening high-purity quartz sand with low gas-liquid inclusions by regulating particle size, surface modification and transparency optimization. This method achieves the screening and graded utilization of quartz raw materials with low gas-liquid inclusion content by sorting by transparency difference, effectively reducing the pollution of quartz sand products by impurities with high gas-liquid inclusions; the Chinese invention patent application with publication number CN117825375A discloses a method for screening high-purity quartz raw materials for quartz crucibles by detecting inclusions and hydroxyl content. This method significantly improves time efficiency and reduces costs. However, the selection of raw materials for high-purity quartz for photovoltaic crucibles in the industry not only has requirements for inclusions, but also has strict requirements for indicators such as purity, impurity elements and particle size. Therefore, the above method is obviously not comprehensive enough to evaluate and screen high-purity quartz raw materials only by the single indicator of inclusions.
[0006] A Chinese invention patent application with publication number CN118641540A discloses a field quality evaluation system for vein quartz ores that collects and analyzes characteristic values of quartz ores and conducts quality and value assessments, which can effectively improve the accuracy of field quality evaluations of vein quartz ores. Although this method proposes an evaluation system based on quartz grain contact relationships, color, light transmittance, mineral composition, and quartz grain uniformity, it lacks evaluation dimensions such as purity and impurity elements and the evaluation is not in-depth. It can only roughly evaluate quartz raw materials in the field and cannot be applied to actual production.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] One of the purposes of the present invention is to provide a method for screening vein quartz type high-purity quartz for photovoltaic crucibles, which realizes a comprehensive evaluation of the applicability of high-purity quartz in the field of photovoltaic crucibles, can replace the traditional crucible test, and solves the problems of inconsistent evaluation and screening standards for high-purity quartz sand and over-reliance on crucible testing to verify applicability.
[0009] The second object of the present invention is to provide an application of a method for screening vein quartz type high-purity quartz for photovoltaic crucibles, which is conducive to achieving efficient utilization of resources.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, a method for screening vein quartz type high-purity quartz for photovoltaic crucibles comprises the following steps: Analyze and grade the mineral composition of the vein quartz ore: when there are no associated minerals in the analyzed mineral composition, it is graded as Class A; Analyze and grade the mineral dissemination of vein quartz ore: when the mineral dissemination is analyzed as independent quartz grains, it is graded as Class A; Analyze and grade the microscopic morphology of pure minerals of vein quartz: when the microscopic morphology is transparent quartz grains without inclusions and associated minerals, it is rated as Class A; Analyze and rate the chemical composition of high-purity quartz purified from vein quartz pure minerals: when the purity of the analyzed chemical composition is ≥99.995%, and the impurities are mainly Al, K and Na, Al>9ppm, K>0.5ppm, Na>1ppm, it is rated as Class A; Analyze and grade the lattice impurities of high-purity quartz purified from vein quartz pure minerals: Measured in ppm of element content, when analyzing the lattice impurities (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+) is between 1 and 3, it is rated as Class A; When no less than 4 Class A ratings are obtained, the vein quartz-type high-purity quartz can be used as a raw material for photovoltaic crucibles, otherwise it cannot be used as a raw material for photovoltaic crucibles.
[0011] Furthermore, when the Class A rating is 5, the vein quartz type high-purity quartz can be used as the inner sand of the photovoltaic crucible; When the A-class rating is 4, the vein quartz type high-purity quartz can be used as the middle and outer layer sand of the photovoltaic crucible.
[0012] Furthermore, the mineral composition analysis method includes identifying the mineral composition of the vein quartz ore by X-ray diffractometer.
[0013] Furthermore, the analysis method of the mineral dissemination includes observing the slices of vein quartz ore through a polarizing microscope to identify the optical properties.
[0014] Furthermore, the analysis method of the microscopic morphology includes observing the pure minerals of vein quartz through a polarizing microscope to identify the morphology, inclusion embedding characteristics and equivalent radius size.
[0015] Furthermore, the vein quartz pure mineral is obtained from the vein quartz ore through the processes of crushing, sand making, screening, magnetic separation and flotation.
[0016] Furthermore, the chemical composition analysis method includes testing high-purity quartz by inductively coupled plasma emission spectrometry.
[0017] Furthermore, the high-purity quartz is obtained by purifying vein quartz pure minerals through acid leaching.
[0018] Furthermore, the analysis method of lattice impurities includes testing high-purity quartz by inductively coupled plasma emission spectrometry.
[0019] In a second aspect, a method for screening vein quartz-type high-purity quartz for photovoltaic crucibles as described in any of the above items is used in the production of photovoltaic crucibles.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects: The screening method of vein quartz type high-purity quartz for photovoltaic crucibles provided by the present invention evaluates and screens high-purity quartz for photovoltaic crucibles through a comprehensive evaluation system. The method comprehensively considers the key factors of mineral composition, mineral embedding state, microscopic morphology, chemical composition and lattice impurities, and can effectively solve the problems of inconsistent current high-purity quartz sand evaluation and screening standards and excessive reliance on traditional crucible testing to verify the applicability of quartz sand. At the same time, it can also significantly reduce unnecessary waste in manpower, material resources and financial resources.
[0021] Application of the screening method of vein quartz type high-purity quartz for photovoltaic crucibles provided by the present invention is conducive to realizing efficient utilization of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A flow chart for the evaluation and screening of vein quartz type high purity quartz provided in one embodiment of the present invention; Figure 2 The XRD diagram provided by Example 1 of the present invention; Figure 3 The rock and mineral identification microphotograph provided in Example 1 of the present invention; Figure 4 Optical microscopic morphology of pure minerals provided in Example 1 of the present invention; Figure 5 A radar chart for evaluating purification potential provided in Example 1 of the present invention; Figure 6 The XRD diagram provided by Example 2 of the present invention; Figure 7 Microscopic photographs of rock and mineral identification provided in Example 2 of the present invention; Figure 8 Optical microscopic morphology of pure minerals provided in Example 2 of the present invention; Fig. 9 A radar chart for evaluating purification potential provided in Example 2 of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In view of the problem that the current evaluation indicators and dimensions are single and incomplete in the evaluation and screening process of high-purity quartz for photovoltaic crucibles, this paper aims to establish an evaluation and screening method for vein quartz type high-purity quartz through the dimensions of vein quartz ore analysis, vein quartz pure mineral analysis and high-purity quartz product analysis, and specially proposes the technical scheme of the present invention.
[0026] According to a first aspect of the present invention, there is provided a method for screening vein quartz type high-purity quartz for photovoltaic crucibles, comprising the following steps: Analyze and grade the mineral composition of the vein quartz ore: when there are no associated minerals in the analyzed mineral composition, it is graded as Class A; Analyze and grade the mineral dissemination of vein quartz ore: when the mineral dissemination is analyzed as independent quartz grains, it is graded as Class A; Analyze and grade the microscopic morphology of pure minerals of vein quartz: when the microscopic morphology is transparent quartz grains without inclusions and associated minerals, it is rated as Class A; Analyze and rate the chemical composition of high-purity quartz purified from vein quartz pure minerals: when the purity of the analyzed chemical composition is ≥99.995%, and the impurities are mainly Al, K and Na, Al>9ppm, K>0.5ppm, Na>1ppm, it is rated as Class A; Analyze and grade the lattice impurities of high-purity quartz purified from vein quartz pure minerals: Measured in ppm of element content, when analyzing the lattice impurities (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+ ) is between 1 and 3, it is rated as Class A; When no less than 4 Class A ratings are obtained, the vein quartz-type high-purity quartz can be used as a raw material for photovoltaic crucibles, otherwise it cannot be used as a raw material for photovoltaic crucibles.
[0027] The present invention can effectively solve the problems of confusion in current high-purity quartz sand evaluation and screening standards and heavy reliance on traditional crucible testing to verify the applicability of quartz sand, and can significantly reduce unnecessary waste in manpower, material resources and financial resources.
[0028] In a preferred embodiment, when the Class A rating is 5, the vein quartz type high purity quartz can be used as the inner sand of the photovoltaic crucible; When the A-level rating is 4, the vein quartz type high-purity quartz can be used as the middle and outer layer sand of photovoltaic crucible.
[0029] In short, if 5 Class A ratings are obtained, it can be considered as a first-level high-purity quartz raw material with the potential for purification as the inner layer sand of photovoltaic crucibles; if 4 Class A ratings are obtained, it can be considered as a second-level high-purity quartz raw material with the potential for purification as the middle and outer layer sand of photovoltaic crucibles; otherwise, it cannot be used for photovoltaic crucible sand.
[0030] In a preferred embodiment, the analysis method of the mineral composition includes but is not limited to identifying the mineral composition of the vein quartz ore by X-ray diffractometer.
[0031] Different gangue mineral compositions will directly affect the difficulty of selecting vein quartz samples. The analysis of mineral composition uses X-ray diffractometer to identify whether there are other gangue minerals in the vein quartz in addition to quartz. At the same time, the mineral composition is rated: when there are no associated minerals, it is rated as Class A; when the main associated mineral is muscovite, it is rated as Class B; when the main associated minerals are muscovite and feldspar, and contain biotite and tourmaline, it is rated as Class C; when the associated mineral content is greater than 5%, there are more than 4 kinds, and it contains biotite and tourmaline, it is rated as Class D.
[0032] In a preferred embodiment, the analysis method of mineral dissemination includes but is not limited to observing vein quartz ore slices through a polarizing microscope, where the thickness of the ore slices may be, for example, 30 µm, and identifying optical properties.
[0033] The type and content of gangue minerals have a significant impact on the interpenetration particle size characteristics of minerals. The finer and more uniform the interpenetration particle size of gangue minerals, the more difficult it is to dissociate quartz monomers, and the more difficult it is to beneficiate and purify minerals. The analysis of mineral interpenetration is to observe quartz ore thin sections with a polarizing microscope, identify their optical properties, and determine the mineral composition and the interpenetration state of associated minerals in quartz. At the same time, the mineral interpenetration is rated: when the mineral interpenetration is mainly independent quartz grains, it is rated as Class A; when the mineral interpenetration is mainly muscovite and feldspar interpenetrated in the cracks between quartz grains, it is rated as Class B; when there are more interpenetrated minerals inside the quartz grains, it is rated as Class C; when there are more columnar interpenetrated minerals and needle-shaped micron-sized solid inclusions inside the quartz grains, it is rated as Class D.
[0034] In a preferred embodiment, the analysis method of microscopic morphology includes but is not limited to observing the pure mineral of vein quartz through a polarizing microscope to identify the morphology, inclusion embedding characteristics and equivalent radius size.
[0035] Among them, vein quartz pure mineral can be obtained from vein quartz ore through crushing, sand making, screening, magnetic separation and flotation processes.
[0036] Polarized light microscope is used to observe and identify the morphology, inclusion embedding characteristics and equivalent radius of pure minerals of quartz sand after physical purification, and judge its purification potential; among them, inclusions include solid inclusions and gas-liquid inclusions, and the smaller the particle size, the more difficult it is to remove. At the same time, the microscopic morphology is rated: when the quartz grains are transparent and there are no inclusions and associated minerals, it is rated as Class A; when the quartz grains are transparent and mainly contain gas-liquid inclusions with a size of ≥2µm, it is rated as Class B; when the quartz grains have dark impregnation layers and mainly contain gas-liquid inclusions with a size of <2µm, it is rated as Class C; when the quartz grains have dark impregnation layers and mainly contain solid inclusions, it is rated as Class D.
[0037] In a preferred embodiment, the chemical composition analysis method includes but is not limited to testing high purity quartz by inductively coupled plasma emission spectrometry.
[0038] In a preferred embodiment, the analysis method of lattice impurities includes but is not limited to testing high purity quartz by inductively coupled plasma optical emission spectrometry.
[0039] Among them, high-purity quartz can be obtained by purifying vein quartz pure minerals through acid leaching.
[0040] Inductively coupled plasma emission spectrometry is used to test and analyze the chemical composition and lattice impurities of high-purity quartz, mainly targeting the small amount of fine-grained gangue minerals, impurity element dissemination and lattice impurities still existing in pure quartz minerals. The content of impurity elements (Al, B, Ba, Ca, Cu, Cr, Fe, K, Li, Mg, Mn, Na, P, Ti) in the acid-leached concentrate is tested and their relative distribution relationship is determined.
[0041] The chemical composition of high-purity quartz is rated as follows: when the chemical purity is ≥99.995%, and the impurities are mainly Al, K and Na, and their contents are Al>9ppm, K>0.5ppm, and Na>1ppm, it is rated as Class A; when the chemical purity is ≥99.99%, and the impurities are mainly Al, K, Na, Fe and Ca, it is rated as Class B; when the chemical purity is ≥99.95%, and the impurities are mainly Al, K, Na, Fe, Mg, Ca and Ti, it is rated as Class C; when the chemical purity is <99.95% and the impurities are complex, it is rated as Class D.
[0042] During the formation of quartz crystals, some elements will replace silicon and enter the quartz crystal, thus forming lattice impurities of quartz. Lattice impurities are closely related to the point defect density of quartz crystals, and it is easy to introduce impurity elements in two different ways: one is to replace Si 4+ Substitution atoms (such as Fe 3+ 、Al 3+ ,Ge 4+ and Ti 4+ ), and the other is the interstitial atoms (such as K + 、Na + , Li + and Ca 2+ ).
[0043] Rating of high purity quartz lattice impurities: measured in ppm of element content, when (Fe 3+ +Al 3+ +B 3+ ) / (K+ +Na + +Li + +P 5+ ) is close to 1 and less than 3, it is rated as Class A; when (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+ )<15, it is rated as Class B; when (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+ )>15, it is rated as Class C; when (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+ )>>15, it is rated as Class D.
[0044] A typical evaluation and screening process for vein quartz type high purity quartz, see Figure 1 , including the following steps: (1) Select representative vein quartz ore, grind it to less than 200 mesh using an agate mortar, analyze the mineral composition of the ore and grade it; (2) Select representative vein quartz ore, observe each area of its slice, analyze the mineral distribution through rock and mineral identification, and make a grade; (3) Select representative vein quartz ore, subject it to crushing, sand making, screening, magnetic separation and flotation processes to obtain pure vein quartz minerals, analyze the microscopic morphology of the pure vein quartz minerals and grade them; (4) further purifying the vein quartz pure mineral obtained in step (3) by acid leaching (high purification process) to obtain high-purity quartz, analyzing the chemical composition and lattice impurities of the high-purity quartz and grading it; (5) Based on the rating results of mineral composition, mineral distribution (i.e. rock and mineral identification), microscopic morphology, chemical composition and lattice impurities, a comprehensive evaluation (whether it has the potential for purification and application) is obtained to determine whether the quartz raw material can be used as high-purity quartz raw material for photovoltaic crucibles, thereby achieving the purpose of screening vein quartz-type high-purity quartz for photovoltaic crucibles.
[0045] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0046] Example 1 This embodiment provides a method for screening vein quartz type high-purity quartz for photovoltaic crucibles, which is to evaluate a certain vein quartz type high-purity quartz in China, and then determine whether it can be used as a raw material for photovoltaic crucibles, including the following steps: (1) Select representative vein quartz ore, grind it to less than 200 mesh using an agate mortar, and perform phase analysis using XRD. Figure 2 As shown, it can be seen that the mineral composition of the sample is single, and its main phase is quartz; (2) Select representative vein quartz ore, prepare thin sections from it, and use a polarizing microscope to observe and analyze each area of the section. Figure 3 As shown, the quartz grains are intact and almost entirely composed of quartz, with a high content of fluid inclusions, mostly distributed in the form of beads; (3) Select representative vein quartz ore, crush it, make sand, screen it, separate it by magnetic separation and flotation to obtain pure vein quartz mineral, and observe the microscopic morphology of the pure vein quartz mineral. Figure 4 As shown, no associated minerals were found under high magnification, but significantly more inclusions were visible in the quartz grains. The inclusions were mostly long strips and ellipses. Under high magnification, the inclusions were mainly gas-liquid inclusions, with more than 85% larger than 2µm in size and 50% larger than 10µm in size. (4) further purifying the vein quartz pure mineral obtained in step (3) by acid leaching to obtain high-purity quartz, and analyzing the chemical composition and lattice impurities of the high-purity quartz; The chemical composition test data are shown in Table 1. After acid leaching, the SiO2 content of quartz sand is 99.998%, and its impurity chemical composition is mainly Al, K and Na; At the same time, in terms of element content ppm, (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+ ) is 2.33, indicating that the lattice impurity content in the vein quartz is low; Table 1 Chemical composition (ppm)
[0047] (5) The rating results of mineral composition, mineral embedding, microscopic morphology, chemical composition and lattice impurities are shown in Table 2. The corresponding radar chart for purification potential evaluation is shown in Figure 5 As shown; Table 2
[0048] If 5 A-level ratings are obtained, it can be considered as a first-level high-purity quartz raw material, which has the potential to be used as the inner layer sand of photovoltaic crucibles; if 4 A-level ratings are obtained, it can be considered as a second-level high-purity quartz raw material, which has the potential to be used as the outer layer sand of photovoltaic crucibles; otherwise, it cannot be used for photovoltaic crucible sand; The sample obtained 4 Class A indicators and belongs to the secondary high-purity quartz raw material. After purification, the purity of the concentrated sand can reach 4N8, indicating that the vein quartz has the purification potential as the middle and outer layer sand of photovoltaic crucible.
[0049] At present, the vein quartz has been mass-produced and sold as crucible outer layer sand, which is consistent with the results obtained by the evaluation and screening of this embodiment.
[0050] Example 2 This embodiment provides a method for screening vein quartz type high-purity quartz for photovoltaic crucibles, which is to evaluate a certain vein quartz type high-purity quartz in China, and then determine whether it can be used as a raw material for photovoltaic crucibles, including the following steps: (1) Select representative vein quartz ore, grind it to less than 200 mesh using an agate mortar, and perform phase analysis using XRD. Figure 6 As shown, the main phase of the sample is quartz, with small amounts of anorthite (2.56%), albite (1.57%) and muscovite (1.39%). (2) Select representative vein quartz ore, prepare thin sections from it, and use a polarizing microscope to observe and analyze each area of the section. Figure 7 As shown, the quartz is anisomorphic with large grain size, and the embedded minerals are mainly muscovite and feldspar embedded in the intercrystalline cracks; (3) Select representative vein quartz ore, crush it, make sand, screen it, separate it by magnetic separation and flotation to obtain pure vein quartz mineral, and observe the microscopic morphology of the pure vein quartz mineral. Figure 8 As shown, obvious inclusions can be seen, mainly gas-liquid inclusions, most of which are larger than 2µm in size; (4) further purifying the vein quartz pure mineral obtained in step (3) by acid leaching to obtain high-purity quartz, and analyzing the chemical composition and lattice impurities of the high-purity quartz; The chemical composition test data are shown in Table 3. After acid leaching, the SiO2 content of quartz sand is 99.995%, and its impurity minerals are mainly Al and Ti; At the same time, in terms of element content ppm, (Fe 3+ +Al 3+ +B 3+ ) / (K ++Na + +Li + +P 5+ ) is 11.72, indicating that the lattice impurity content in the vein quartz is relatively high; Table 3 Chemical composition (ppm)
[0051] (5) The rating results of mineral composition, mineral embedding, microscopic morphology, chemical composition and lattice impurities are shown in Table 4. The corresponding radar chart for purification potential evaluation is shown in Fig. 9 As shown; Table 4
[0052] If 5 A-level ratings are obtained, it can be considered as a first-level high-purity quartz raw material, which has the potential to be used as the inner layer sand of photovoltaic crucibles; if 4 A-level ratings are obtained, it can be considered as a second-level high-purity quartz raw material, which has the potential to be used as the outer layer sand of photovoltaic crucibles; otherwise, it cannot be used for photovoltaic crucible sand; The sample obtained 4 Class B indicators and 1 Class C indicator, indicating that the vein quartz is not suitable for use as photovoltaic crucible sand.
[0053] Currently, the vein quartz has been purified and sold as electronic sand, which is consistent with the results obtained by the evaluation and screening of this embodiment.
[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for screening vein quartz type high-purity quartz for photovoltaic crucibles, characterized in that: The following steps are involved: Analyze and grade the mineral composition of the vein quartz ore: when there are no associated minerals in the analyzed mineral composition, it is graded as Class A; Analyze and grade the mineral dissemination of vein quartz ore: when the mineral dissemination is analyzed as independent quartz grains, it is graded as Class A; Analyze and grade the microscopic morphology of pure minerals of vein quartz: when the microscopic morphology is transparent quartz grains without inclusions and associated minerals, it is rated as Class A; Analyze and rate the chemical composition of high-purity quartz purified from vein quartz pure minerals: when the purity of the analyzed chemical composition is ≥99.995%, and the impurities are mainly Al, K and Na, Al>9ppm, K>0.5ppm, Na>1ppm, it is rated as Class A; Analyze and grade the lattice impurities of high-purity quartz purified from vein quartz pure minerals: Measured in ppm of element content, when analyzing the lattice impurities (Fe 3+ +Al 3+ +B 3+ ) / (K + +Na + +Li + +P 5+ ) is between 1 and 3, it is rated as Class A; When no less than 4 Class A ratings are obtained, the vein quartz-type high-purity quartz can be used as a raw material for photovoltaic crucibles, otherwise it cannot be used as a raw material for photovoltaic crucibles.
2. The screening method according to claim 1, characterized in that When the A-class rating is 5, the vein quartz type high-purity quartz can be used as the inner sand of the photovoltaic crucible; When the A-class rating is 4, the vein quartz type high-purity quartz can be used as the middle and outer layer sand of the photovoltaic crucible.
3. The screening method according to claim 1, characterized in that The method for analyzing the mineral composition includes identifying the mineral composition of the vein quartz ore by an X-ray diffractometer.
4. The screening method according to claim 1, characterized in that The method for analyzing the mineral dissemination includes observing a slice of the vein quartz ore through a polarizing microscope to identify the optical properties.
5. The screening method according to claim 1, characterized in that The microscopic morphology analysis method includes observing the vein quartz pure minerals through a polarizing microscope to identify the morphology, inclusion embedding characteristics and equivalent radius size.
6. The screening method according to claim 5, characterized in that The vein quartz pure mineral is obtained from vein quartz raw ore through the processes of crushing, sand making, screening, magnetic separation and flotation.
7. The screening method according to claim 1, characterized in that The chemical composition analysis method includes testing high purity quartz by inductively coupled plasma emission spectrometry.
8. The screening method according to claim 7, characterized in that The high-purity quartz is obtained by purifying vein quartz pure minerals through acid leaching.
9. The screening method according to claim 1, characterized in that The analysis method of lattice impurities includes testing high-purity quartz by inductively coupled plasma emission spectrometry.
10. Use of the screening method according to any one of claims 1 to 9 in the production of photovoltaic crucibles.
Citation Information
Patent Citations
Method for selecting high-purity quartz raw material for quartz crucible
CN117825375A
Quartz sand evaluation method for quartz glass crucible
CN117849052A